Fighting nature: Travelling menageries, animal acts and war shows - Tait, Peta (Animal Publics, 2015)
Fighting Nature is an insightful analysis of the historical legacy of 19th century colonialism, war, animal acquisition and transportation. This legacy of entrenched beliefs about the human right to exploit other animal species is yet to be defeated. Throughout the 19th century animals were integrated into staged scenarios of confrontation, ranging from lion acts in small cages to large-scale re-enactments of war. Initially presenting a handful of exotic animals, travelling menageries grew to contain multiple species in their thousands. These 19th-century menageries entrenched beliefs about the human right to exploit nature through war-like practices against other animal species. Animal shows became a stimulus for antisocial behaviour as locals taunted animals, caused fights, and even turned into violent mobs. Human societal problems were difficult to separate from issues of cruelty to animals.